2009
DOI: 10.1001/archinternmed.2009.11
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width and the Risk of Death in Middle-aged and Older Adults

Abstract: Background Red cell distribution width (RDW), a component of an electronic complete blood count, is a measure of heterogeneity in the size of circulating erythrocytes. In patients with symptomatic cardiovascular disease (CVD), RDW is associated with mortality. However, it has not been demonstrated that RDW is a predictor of mortality independent of nutritional deficiencies or in the general population. Methods RDW was measured in a national sample of 8175 community-dwelling adults aged 45 and older who parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
469
9
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 542 publications
(517 citation statements)
references
References 21 publications
16
469
9
13
Order By: Relevance
“…Although higher RDW levels have been related to cardiovascular morbidity and mortality in several study populations [4][5][6][7], RDW has not been studied as a marker of complications in diabetes. In the present investigation, we used the NHANES III database to demonstrate a relationship between RDW and CVD in a selected diabetes population that is representative of approximately 18 million USA adults aged 20 years and older.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although higher RDW levels have been related to cardiovascular morbidity and mortality in several study populations [4][5][6][7], RDW has not been studied as a marker of complications in diabetes. In the present investigation, we used the NHANES III database to demonstrate a relationship between RDW and CVD in a selected diabetes population that is representative of approximately 18 million USA adults aged 20 years and older.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is possible that microvascular disease and the related inflammatory process of retinopathy may occur mostly at the local tissue level and not be related to systemic inflammation [18,26]. Since RDW seems to reflect systemic inflammatory processes known to affect the macrovasculature [6,24], this may explain, at least partially, its relationship with macrovascular but not microvascular disease processes. Previous prospective studies have described a role of RDW as a predictive marker for CVD morbidity and mortality in several populations [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous studies and a meta-analysis demonstrated that RDW is a potent predictor of all-cause mortality, including cancer-related deaths (Patel et al, 2009;Perlstein et al, 2009;Patel et al, 2010). There is also a strong, graded association between RDW and inflammatory biomarkers (fibrinogen, serum C-reactive protein [CRP], and erythrocyte sedimentation rate [ESR]), which is independent of numerous confounding factors (Cakal et al, 2009;Lippi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%